A titanium dioxide-based ceramic material with high thermal stability and a preparation method thereof

By adding specific rare earth oxides and nano-excipients to titanium dioxide-based ceramic materials and adopting reasonable preparation processes, the problem that existing materials are difficult to meet the needs of high dielectric constant, low dielectric loss and high thermal stability at the same time is solved, and the dielectric properties and wear resistance of ceramic materials have been greatly improved.

CN119285349BActive Publication Date: 2025-04-15苏州芯合半导体材料有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411832630.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-15
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing titanium dioxide-based ceramic materials are difficult to meet the needs of high dielectric constant, low dielectric loss and high thermal stability at the same time, and the wear resistance is insufficient, making it difficult to meet the needs of high-stability capacitor products.

Method used

A ceramic material including a titanium dioxide-based ceramic matrix, nano-excipients and binding additives is used to prepare a high-thermal stability titanium dioxide-based ceramic material by reasonably selecting raw materials such as rare earth oxides and alumina, and performing ball milling, granulation, tableting, glue discharge and sintering during the preparation process.

Benefits of technology

It achieves high dielectric constant, low dielectric loss, good thermal stability and excellent wear resistance of ceramic materials, and meets the needs of high-stability capacitor products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention discloses a titanium dioxide-based ceramic material with high thermal stability and a preparation method thereof, and relates to the technical field of ceramic materials. The material comprises the following components by weight: 75-85 parts of a titanium dioxide-based ceramic matrix, 5-10 parts of a nano auxiliary material, and 1-3 parts of a bonding aid; the titanium dioxide-based ceramic matrix comprises the following raw materials: rare earth oxide, strontium carbonate, aluminum oxide, hafnium oxide, germanium oxide, molybdenum oxide, cobalt oxide, boron oxide, tellurium oxide, vanadium oxide, iridium oxide, and titanium dioxide. The ceramic material has high dielectric constant, low dielectric loss, good thermal stability, and excellent wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to a titanium dioxide-based ceramic material with high thermal stability and a preparation method thereof. Background Art

[0002] With the demand for miniaturization, integration and intelligence of ceramic capacitors and microwave dielectric components in the microelectronics market, functional ceramic materials with high dielectric constant, low loss and good thermal stability have attracted more and more attention. As a representative of many functional ceramic materials, titanium dioxide-based ceramic materials with high dielectric constant have been widely used in many fields such as capacitors, memory, and microelectronic components.

[0003] Most of the existing titanium dioxide-based ceramic materials cannot meet the requirements of high dielectric constant and low dielectric loss at the same time, and have low thermal stability, making it difficult to meet the needs of high-stability capacitor products. In order to solve the above problems, a Chinese invention patent with authorization announcement number CN109133914B discloses a titanium dioxide-based ceramic material with high thermal stability and a preparation method thereof. The general formula of the ceramic material is , where M represents Nb or Ta, and x is 0.005 to 0.02. The preparation method of the ceramic material of the invention is simple, repeatable and has a high yield. By introducing CuNb or CuTa into the titanium dioxide-based ceramic material, the ceramic material can be It has a high dielectric constant and low dielectric loss in the range, where when x=0.005, the dielectric loss is always kept below 0.08 in the frequency test range. It also has high thermal stability. In the temperature range of -200 to 200°C, CuNb or CuTa co-doped titanium dioxide ceramics meet the application requirements of X9F and X9E ceramic capacitors respectively. Compared with X9R ceramic capacitors, the invented ceramic material has a lower capacitance change rate, stronger thermal stability and practicality, and is expected to be applied to the electronic market such as multilayer ceramic capacitors. However, there is still room for improvement in its dielectric loss and thermal stability, and its wear resistance needs to be further improved.

[0004] It can be seen that the development of a high dielectric constant, low dielectric loss, good thermal stability, excellent wear resistance and high thermal stability titanium dioxide-based ceramic material and its preparation method meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the field of titanium dioxide-based ceramic materials. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a titanium dioxide-based ceramic material with high thermal stability, high dielectric constant, low dielectric loss, good thermal stability and excellent wear resistance, and a preparation method thereof.

[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a titanium dioxide-based ceramic material with high thermal stability, comprising the following components in parts by weight: 75-85 parts of a titanium dioxide-based ceramic matrix, 5-10 parts of a nano-auxiliary material, and 1-3 parts of a bonding aid; the titanium dioxide-based ceramic matrix comprises the following raw materials in weight percentage: 2wt%-6wt% of rare earth oxide, 0.2wt%-0.8wt% of strontium carbonate, 1wt%-3wt% of aluminum oxide, 0.8wt%-1.2wt% of hafnium oxide, 0.1wt%-0.5wt% of germanium oxide, 0.8wt%-1.2wt% of molybdenum oxide, 1wt%-1.5wt% of cobalt oxide, 0.03wt%-0.1wt% of boron oxide, 0.01wt%-0.03wt% of tellurium oxide, 0.8wt%-1.2wt% of vanadium oxide, 0.03wt%-0.06wt% of iridium oxide, and the balance is titanium dioxide.

[0007] Preferably, the rare earth oxide is at least one of yttrium oxide, scandium oxide, cerium oxide and praseodymium oxide.

[0008] Preferably, the nano auxiliary material is at least one of nano tantalum boride and nano niobium nitride.

[0009] Preferably, the bonding aid comprises the following raw materials in parts by weight: 3-5 parts of (3,6-diaminoacridine-9-yl)boric acid, 1-3 parts of hydroxypropyl β-cyclodextrin, and 0.1-0.3 parts of adenosine.

[0010] Preferably, the particle size of the titanium dioxide-based ceramic matrix is ​​5-15 μm.

[0011] Preferably, the average particle size of the nano auxiliary material is 10-80nm.

[0012] Another object of the present invention is to provide a method for preparing the titanium dioxide-based ceramic material with high thermal stability, comprising the following steps:

[0013] Step S1, mixing the raw materials of the titanium dioxide-based ceramic matrix according to weight percentage, and then ball milling, drying, and pre-sintering to obtain the titanium dioxide-based ceramic matrix;

[0014] Step S2, uniformly mixing the titanium dioxide-based ceramic matrix, nano-auxiliary materials, and bonding aid prepared in step S1 according to weight portions to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0015] Step S3, granulating, tableting, and debinding the uniform powder obtained in step S2 in sequence, and then sintering to obtain a titanium dioxide-based ceramic material with high thermal stability.

[0016] Preferably, the ball milling time in step S1 is 10-20 hours, the drying temperature is 85-100° C., and the time is 10-20 hours; the pre-calcination temperature is 990-1180° C., and the time is 4-8 hours, and it is carried out under closed conditions.

[0017] Preferably, the tableting in step S3 is performed by using a powder tablet press at a pressure of 8 to 12 MPa for 4 to 8 minutes.

[0018] Preferably, the debinding in step S3 is performed under a vacuum environment, the debinding temperature is 500-600° C., the holding time is 2-4 h, and the debinding heating rate is 0.1-1° C. / min.

[0019] Preferably, the sintering treatment conditions in step S3 are: sintering at 1350-1650° C. for 8-12 hours in a nitrogen atmosphere and sealed conditions.

[0020] Due to the application of the above technical solution, the present invention has the following beneficial effects:

[0021] (1) The method for preparing the titanium dioxide-based ceramic material with high thermal stability disclosed in the present invention has simple process, convenient operation and control, good repeatability, high yield rate, is suitable for continuous large-scale production, and has high promotion and application value.

[0022] (2) The titanium dioxide-based ceramic material with high thermal stability disclosed in the present invention comprises the following components in parts by weight: 75-85 parts of a titanium dioxide-based ceramic matrix, 5-10 parts of a nano-auxiliary material, and 1-3 parts of a bonding agent; the titanium dioxide-based ceramic matrix comprises the following raw materials in percentage by weight: 2wt%-6wt% of rare earth oxide, 0.2wt%-0.8wt% of strontium carbonate, 1wt%-3wt% of aluminum oxide, 0.8wt%-1.2wt% of hafnium oxide, 0.1wt%-0.5wt% of germanium oxide, 0.8wt%-1.2wt% of molybdenum oxide, 1wt%-1.5wt% of cobalt oxide, 0.03wt%-0.1wt% of boron oxide, 0.01wt%-0.03wt% of tellurium oxide, 0.8wt%-1.2wt% of vanadium oxide, 0.03wt%-0.06wt% of iridium oxide, and the balance is titanium dioxide. Through the mutual coordination and joint action of various components and raw materials, the manufactured ceramic material has a high dielectric constant, low dielectric loss, good thermal stability and excellent wear resistance.

[0023] (3) The titanium dioxide-based ceramic material with high thermal stability disclosed in the present invention, wherein the nano auxiliary material is at least one of nano tantalum boride and nano niobium nitride; the bonding aid comprises the following raw materials in parts by weight: 3-5 parts of (3,6-diaminoacridine-9-yl)boric acid, 1-3 parts of hydroxypropyl β-cyclodextrin, and 0.1-0.3 parts of adenosine. By rationally selecting the types and composition formulas of the components in the ceramic material formula, the dielectric constant can be further improved and the dielectric loss can be reduced; in addition, the internal density of the ceramic material can be improved, and the wear resistance and thermal stability of the ceramic material can be improved.

[0024] (4) The titanium dioxide-based ceramic material with high thermal stability disclosed in the present invention has better wear resistance, higher dielectric constant, lower dielectric loss and better thermal stability through reasonable selection of various process parameters during the preparation process. DETAILED DESCRIPTION

[0025] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0026] Example 1, a titanium dioxide-based ceramic material with high thermal stability, comprising the following components in parts by weight: 75 parts of a titanium dioxide-based ceramic matrix, 5 parts of a nano-auxiliary material, and 1 part of a bonding aid; the titanium dioxide-based ceramic matrix comprises the following raw materials in percentage by weight: 2wt% rare earth oxide, 0.2wt% strontium carbonate, 1wt% aluminum oxide, 0.8wt% hafnium oxide, 0.1wt% germanium oxide, 0.8wt% molybdenum oxide, 1wt% cobalt oxide, 0.03wt% boron oxide, 0.01wt% tellurium oxide, 0.8wt% vanadium oxide, 0.03wt% iridium oxide, and the balance is titanium dioxide.

[0027] The rare earth oxide is yttrium oxide; the nano auxiliary material is nano tantalum boride; the bonding aid comprises the following raw materials in parts by weight: 3 parts of (3,6-diaminoacridine-9-yl)boric acid, 1 part of hydroxypropyl β-cyclodextrin, and 0.1 parts of adenosine; the particle size of the titanium dioxide-based ceramic matrix is ​​5 μm; and the average particle size of the nano auxiliary material is 10 nm.

[0028] A method for preparing the titanium dioxide-based ceramic material with high thermal stability comprises the following steps:

[0029] Step S1, mixing the raw materials of the titanium dioxide-based ceramic matrix according to weight percentage, and then ball milling, drying, and pre-sintering to obtain the titanium dioxide-based ceramic matrix;

[0030] Step S2, uniformly mixing the titanium dioxide-based ceramic matrix, nano-auxiliary materials, and bonding aid prepared in step S1 according to weight portions to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0031] Step S3, granulating, tableting, and debinding the uniform powder obtained in step S2 in sequence, and then sintering to obtain a titanium dioxide-based ceramic material with high thermal stability.

[0032] The ball milling time in step S1 is 10 hours, the drying temperature is 85°C and the time is 10 hours; the pre-calcination temperature is 990°C and the time is 4 hours, which are carried out under closed conditions; the tableting in step S3 is carried out by using a powder tablet press at a pressure of 8MPa for 4 minutes.

[0033] The debinding in step S3 is carried out under vacuum, the debinding temperature is 500°C, the holding time is 2h, and the debinding heating rate is 0.1°C / min; the sintering conditions in step S3 are: sintering at 1350°C for 8 hours in a nitrogen atmosphere and sealed conditions.

[0034] Example 2, a titanium dioxide-based ceramic material with high thermal stability, comprising the following components in parts by weight: 77 parts of a titanium dioxide-based ceramic matrix, 6 parts of a nano-auxiliary material, and 1.5 parts of a bonding aid; the titanium dioxide-based ceramic matrix comprises the following raw materials in percentage by weight: 3wt% rare earth oxide, 0.4wt% strontium carbonate, 1.5wt% aluminum oxide, 0.9wt% hafnium oxide, 0.2wt% germanium oxide, 0.9wt% molybdenum oxide, 1.2wt% cobalt oxide, 0.05wt% boron oxide, 0.015wt% tellurium oxide, 0.9wt% vanadium oxide, 0.04wt% iridium oxide, and the balance is titanium dioxide.

[0035] The rare earth oxide is scandium oxide; the nano auxiliary material is nano niobium nitride; the bonding aid comprises the following raw materials in parts by weight: 3.5 parts of (3,6-diaminoacridine-9-yl)boric acid, 1.5 parts of hydroxypropyl β-cyclodextrin, and 0.15 parts of adenosine; the particle size of the titanium dioxide-based ceramic matrix is ​​8 μm; and the average particle size of the nano auxiliary material is 30 nm.

[0036] A method for preparing the titanium dioxide-based ceramic material with high thermal stability comprises the following steps:

[0037] Step S1, mixing the raw materials of the titanium dioxide-based ceramic matrix according to weight percentage, and then ball milling, drying, and pre-sintering to obtain the titanium dioxide-based ceramic matrix;

[0038] Step S2, uniformly mixing the titanium dioxide-based ceramic matrix, nano-auxiliary materials, and bonding aid prepared in step S1 according to weight portions to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0039] Step S3, granulating, tableting, and debinding the uniform powder obtained in step S2 in sequence, and then sintering to obtain a titanium dioxide-based ceramic material with high thermal stability.

[0040] In step S1, the ball milling time is 13 hours, the drying temperature is 88° C., and the time is 13 hours; the pre-calcination temperature is 1030° C., and the time is 5 hours, and it is carried out under closed conditions.

[0041] The tableting described in step S3 is carried out by holding the pressure of 9MPa for 5 minutes using a powder tablet press; the debinding described in step S3 is carried out in a vacuum environment, the debinding temperature is 530°C, the holding time is 2.5h, and the debinding heating rate is 0.4°C / min; the sintering treatment conditions described in step S3 are: sintering at 1450°C for 9 hours in a nitrogen atmosphere and closed conditions.

[0042] Example 3, a titanium dioxide-based ceramic material with high thermal stability, comprising the following components in parts by weight: 80 parts of a titanium dioxide-based ceramic matrix, 7.5 parts of nano-auxiliary materials, and 2 parts of a bonding aid; the titanium dioxide-based ceramic matrix comprises the following raw materials in percentage by weight: 4wt% rare earth oxide, 0.5wt% strontium carbonate, 2wt% aluminum oxide, 1wt% hafnium oxide, 0.35wt% germanium oxide, 1wt% molybdenum oxide, 1.3wt% cobalt oxide, 0.06wt% boron oxide, 0.02wt% tellurium oxide, 1wt% vanadium oxide, 0.045wt% iridium oxide, and the balance is titanium dioxide.

[0043] The rare earth oxide is cerium oxide; the nano auxiliary material is nano tantalum boride; the bonding auxiliary agent comprises the following raw materials in parts by weight: 4 parts of (3,6-diaminoacridine-9-yl)boric acid, 2 parts of hydroxypropyl β-cyclodextrin, and 0.2 parts of adenosine; the particle size of the titanium dioxide-based ceramic matrix is ​​10 μm; and the average particle size of the nano auxiliary material is 50 nm.

[0044] A method for preparing the titanium dioxide-based ceramic material with high thermal stability comprises the following steps:

[0045] Step S1, mixing the raw materials of the titanium dioxide-based ceramic matrix according to weight percentage, and then ball milling, drying, and pre-sintering to obtain the titanium dioxide-based ceramic matrix;

[0046] Step S2, uniformly mixing the titanium dioxide-based ceramic matrix, nano-auxiliary materials, and bonding aid prepared in step S1 according to weight portions to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0047] Step S3, granulating, tableting, and debinding the uniform powder obtained in step S2 in sequence, and then sintering to obtain a titanium dioxide-based ceramic material with high thermal stability.

[0048] In step S1, the ball milling time is 15 hours, the drying temperature is 93° C., and the time is 15 hours; the pre-calcination temperature is 1100° C., and the time is 6 hours, and it is carried out under closed conditions.

[0049] The tableting described in step S3 is carried out by using a powder tablet press at a pressure of 10MPa for 6 minutes; the debinding described in step S3 is carried out in a vacuum environment, the debinding temperature is 550°C, the holding time is 3h, and the debinding heating rate is 0.6°C / min; the sintering treatment conditions described in step S3 are: sintering at 1500°C for 10 hours under nitrogen atmosphere and closed conditions.

[0050] Example 4, a titanium dioxide-based ceramic material with high thermal stability, comprising the following components in parts by weight: 83 parts of a titanium dioxide-based ceramic matrix, 9 parts of a nano-auxiliary material, and 2.5 parts of a bonding aid; the titanium dioxide-based ceramic matrix comprises the following raw materials in percentage by weight: 5.5wt% rare earth oxide, 0.7wt% strontium carbonate, 2.5wt% aluminum oxide, 1.1wt% hafnium oxide, 0.4wt% germanium oxide, 1.1wt% molybdenum oxide, 1.4wt% cobalt oxide, 0.09wt% boron oxide, 0.025wt% tellurium oxide, 1.1wt% vanadium oxide, 0.05wt% iridium oxide, and the balance is titanium dioxide.

[0051] The rare earth oxide is a mixture of yttrium oxide, scandium oxide, cerium oxide and praseodymium oxide in a mass ratio of 1:2:2:1; the nano auxiliary material is a mixture of nano tantalum boride and nano niobium nitride in a mass ratio of 3:5; the bonding aid comprises the following raw materials in parts by weight: 4.5 parts of (3,6-diaminoacridine-9-yl)boric acid, 2.5 parts of hydroxypropyl β-cyclodextrin and 0.25 parts of adenosine; the particle size of the titanium dioxide-based ceramic matrix is ​​13 μm; and the average particle size of the nano auxiliary material is 70 nm.

[0052] A method for preparing the titanium dioxide-based ceramic material with high thermal stability comprises the following steps:

[0053] Step S1, mixing the raw materials of the titanium dioxide-based ceramic matrix according to weight percentage, and then ball milling, drying, and pre-sintering to obtain the titanium dioxide-based ceramic matrix;

[0054] Step S2, uniformly mixing the titanium dioxide-based ceramic matrix, nano-auxiliary materials, and bonding aid prepared in step S1 according to weight portions to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0055] Step S3, granulating, tableting, and debinding the uniform powder obtained in step S2 in sequence, and then sintering to obtain a titanium dioxide-based ceramic material with high thermal stability.

[0056] The ball milling time in step S1 is 18 hours, the drying temperature is 98°C, and the time is 18 hours; the pre-burning temperature is 1160°C, the time is 7.5 hours, and it is carried out under closed conditions; the tableting in step S3 is carried out by using a powder tablet press to maintain the pressure at 11MPa for 7.5 minutes; the debinding in step S3 is carried out in a vacuum environment, the debinding temperature is 590°C, the holding time is 3.5 hours, and the debinding heating rate is 0.9°C / min; the sintering treatment conditions in step S3 are: sintering at 1600°C for 11 hours under nitrogen atmosphere and closed conditions.

[0057] Example 5, a titanium dioxide-based ceramic material with high thermal stability, comprising the following components in parts by weight: 85 parts of a titanium dioxide-based ceramic matrix, 10 parts of a nano-auxiliary material, and 3 parts of a bonding aid; the titanium dioxide-based ceramic matrix comprises the following raw materials in percentage by weight: 6wt% rare earth oxide, 0.8wt% strontium carbonate, 3wt% aluminum oxide, 1.2wt% hafnium oxide, 0.5wt% germanium oxide, 1.2wt% molybdenum oxide, 1.5wt% cobalt oxide, 0.1wt% boron oxide, 0.03wt% tellurium oxide, 1.2wt% vanadium oxide, 0.06wt% iridium oxide, and the balance is titanium dioxide.

[0058] The rare earth oxide is praseodymium oxide; the nano auxiliary material is nano tantalum boride; the bonding aid comprises the following raw materials in parts by weight: 5 parts of (3,6-diaminoacridine-9-yl)boric acid, 3 parts of hydroxypropyl β-cyclodextrin, and 0.3 parts of adenosine; the particle size of the titanium dioxide-based ceramic matrix is ​​15 μm; and the average particle size of the nano auxiliary material is 80 nm.

[0059] A method for preparing the titanium dioxide-based ceramic material with high thermal stability comprises the following steps:

[0060] Step S1, mixing the raw materials of the titanium dioxide-based ceramic matrix according to weight percentage, and then ball milling, drying, and pre-sintering to obtain the titanium dioxide-based ceramic matrix;

[0061] Step S2, uniformly mixing the titanium dioxide-based ceramic matrix, nano-auxiliary materials, and bonding aid prepared in step S1 according to weight portions to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder;

[0062] Step S3, granulating, tableting, and debinding the uniform powder obtained in step S2 in sequence, and then sintering to obtain a titanium dioxide-based ceramic material with high thermal stability.

[0063] In step S1, the ball milling time is 20 hours, the drying temperature is 100° C., and the time is 20 hours; the pre-calcination temperature is 1180° C., and the time is 8 hours, and it is carried out under closed conditions.

[0064] The tableting described in step S3 is carried out by using a powder tablet press at a pressure of 12MPa for 8 minutes; the debinding described in step S3 is carried out in a vacuum environment, the debinding temperature is 600°C, the holding time is 4h, and the debinding heating rate is 1°C / min; the sintering treatment conditions described in step S3 are: sintering at 1650°C for 12 hours in a nitrogen atmosphere and closed conditions.

[0065] Comparative Example 1, a titanium dioxide-based ceramic material with high thermal stability, is substantially the same as Example 1, except that tellurium oxide, germanium oxide and (3,6-diaminoacridine-9-yl)boric acid are not added.

[0066] Comparative Example 2, a titanium dioxide-based ceramic material with high thermal stability, is substantially the same as Example 1, except that iridium oxide, hafnium oxide and adenosine are not added.

[0067] In order to further illustrate the beneficial technical effects of the titanium dioxide-based ceramic materials with high thermal stability involved in each embodiment of the present invention, relevant performance tests were carried out on the titanium dioxide-based ceramic materials with high thermal stability involved in Examples 1-5 and Comparative Examples 1-2. The test results are shown in Table 1. The test method is as follows: the surface of the ceramic material prepared in each example was ground and polished to a thickness of 0.5 mm, ultrasonically wiped clean, and a silver paste with a thickness of 0.02 mm was coated on the upper and lower surfaces respectively, placed in a muffle furnace at 840°C for 30 minutes, and naturally cooled to room temperature. The dielectric properties of the ceramic materials were tested using a Cuilient 4294A precision impedance analyzer and an E4980A LCR tester. Wear resistance is represented by linear wear rate, which is tested using an MM-1000 friction tester. The test conditions are: inertia , specific pressure , linear speed 25m / s.

[0068]

[0069] As can be seen from Table 1, the titanium dioxide-based ceramic material with high thermal stability involved in the embodiment of the present invention has better wear resistance and thermal stability than the comparative example product, and has a higher dielectric constant and lower dielectric loss; the combined use of tellurium oxide, germanium oxide, (3,6-diaminoacridine-9-yl)boric acid, iridium oxide, hafnium oxide and adenosine is beneficial to improving the above properties.

[0070] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A titanium dioxide-based ceramic material with high thermal stability, characterized in that: The invention comprises the following components in parts by weight: 75-85 parts of a titanium dioxide-based ceramic matrix, 5-10 parts of a nano auxiliary material, and 1-3 parts of a bonding agent; the titanium dioxide-based ceramic matrix comprises the following raw materials in percentage by weight: 2wt%-6wt% of rare earth oxide, 0.2wt%-0.8wt% of strontium carbonate, 1wt%-3wt% of aluminum oxide, 0.8wt%-1.2wt% of hafnium oxide, 0.1wt%-0.5wt% of germanium oxide, 0.8wt%-1.2wt% of molybdenum oxide, and 1wt% of cobalt oxide. -1.5wt%, 0.03wt%-0.1wt% boron oxide, 0.01wt%-0.03wt% tellurium oxide, 0.8wt%-1.2wt% vanadium oxide, 0.03wt%-0.06wt% iridium oxide, and the balance is titanium dioxide; the nano auxiliary material is at least one of nano tantalum boride and nano niobium nitride; the bonding aid comprises the following raw materials in parts by weight: 3-5 parts of (3,6-diaminoacridine-9-yl)boric acid, 1-3 parts of hydroxypropyl β-cyclodextrin, and 0.1-0.3 parts of adenosine.

2. The titanium dioxide-based ceramic material with high thermal stability according to claim 1, characterized in that: The rare earth oxide is at least one of yttrium oxide, scandium oxide, cerium oxide and praseodymium oxide.

3. The titanium dioxide-based ceramic material with high thermal stability according to claim 1, characterized in that: The particle size of the titanium dioxide-based ceramic matrix is ​​5-15 μm.

4. The titanium dioxide-based ceramic material with high thermal stability according to claim 1, characterized in that: The average particle size of the nano auxiliary material is 10-80nm.

5. A method for preparing a titanium dioxide-based ceramic material with high thermal stability according to any one of claims 1 to 4, characterized in that: The steps include: Step S1, mixing the raw materials of the titanium dioxide-based ceramic matrix according to weight percentage, and then ball milling, drying, and pre-sintering to obtain the titanium dioxide-based ceramic matrix; Step S2, uniformly mixing the titanium dioxide-based ceramic matrix, nano-auxiliary materials, and bonding aid prepared in step S1 according to weight portions to obtain a mixed material, and ball-milling the mixed material to obtain a uniform powder; Step S3, granulating, tableting, and debinding the uniform powder obtained in step S2 in sequence, and then sintering to obtain a titanium dioxide-based ceramic material with high thermal stability.

6. The method for preparing a titanium dioxide-based ceramic material with high thermal stability according to claim 5, characterized in that: In step S1, the ball milling time is 10-20 hours, the drying temperature is 85-100° C., and the time is 10-20 hours; the pre-calcination temperature is 990-1180° C., and the time is 4-8 hours, and it is carried out under closed conditions.

7. The method for preparing a titanium dioxide-based ceramic material with high thermal stability according to claim 5, characterized in that: The tableting in step S3 is performed by using a powder tablet press at a pressure of 8 to 12 MPa for 4 to 8 minutes; the debinding in step S3 is performed under a vacuum environment, the debinding temperature is 500-600°C, the holding time is 2-4h, and the debinding heating rate is 0.1-1°C / min.

8. The method for preparing a titanium dioxide-based ceramic material with high thermal stability according to claim 5, characterized in that: The sintering treatment conditions in step S3 are: sintering at 1350-1650° C. for 8-12 hours in a nitrogen atmosphere and sealed conditions.

Citation Information

Patent Citations

  • A titanium dioxide-based ceramic material with high thermal stability and its preparation method

    CN109133914B

  • Low temperature microwave medium ceramic material without glass phase addition

    CN101456724A

  • Glass ceramics and process for production thereof, process for producing sintered glass ceramics, process for producing complex, molded article having photocatalytic function, and hydrophilic molded article

    CN102177102A